Analysis of Sharia Marketing Mix in Increasing Business Income of Laying Duck Farmers in East Lebeng Pasongsongan - Silfia Eka Wardani Putri; Nur Afifatuz Zahroh (Alkasb: Journal of Islamic Economics, 2023)
Currently being a laying duck farmer is a profession that is in demand by the villagers to increase their income so that they can meet their daily needs. However, due to their incompetence in marketing their products, the farmers didn’t get the expected profit and even suffered loss, while marketing is the key to success in a business. Therefore, in this study, we analyzed the Islamic marketing mix factor as a determining factor in increasing income. This study used qualitative method to explore the Islamic marketing mix in increasing the income of the laying duck business in Lebeng Timur, Pasongsongan, Sumenep. The data is collected through observation, interviews, documentation, while the method of analysis used descriptive analysis. This research showed that before the pandemic the income of farmers was very good, so they could meet their needs, but due the covid-19 pandemic, the price of duck eggs has decreased and the price of animal feed has increased. It made the marketing was low and made their income so small. Using an Islamic marketing mix that applies the four properties of the Prophet, namely Shiddiq, Amanah, Fathonah and Tabligh can help farmers in marketing, namely the products are taken by subscription or continuous by the collector, making it easier for farmers in selling even in pandemic Covid-19 condition.